Aortopulmonary Window Device Closure - Chandrakant Chavan; Ashish Trivedi; Rajesh Badani (Journal of the Practice of Cardiovascular Sciences, 2024)
Aortopulmonary window (APW) is an uncommon congenital cardiac defect. Most infants presenting with APW will undergo conventional surgical repair. Experience with transcatheter closure of APW is limited. We report the case of a 5-year-old boy with APW, in whom transcatheter closure was performed successfully using Amplatzer ductal occluder device.